Anti-alcoholism drug disulfiram for targeting glioma energy metabolism using BBB-penetrating delivery of fixed-dose combination. (June 2022) - Zhao, Pengfei; Qu, Jingkun; Wu, Aihua; Wang, Shuang; Tang, Xueping; Ou, Ante; Zhang, Jiaxin; Xu, Yi; Zhao, Qiang; Huang, Yongzhuo
Highlights: It was demonstrated a two-pronged strategy of ATP energy depletion for anti-glioma. It was revealed that the ATP depletion by ALDH1L1 inhibition is a new molecular mechanism of disulfiram. A BBB-penetrating protein-based nanohybrid was developed to achieve a fixed-dose ratio delivery for combination therapy. Graphical Abstract: ga1 Abstract: The interconnection between tumor metabolism and the immune microenvironment governs the progression of glioma. It was revealed that the metabolic enzymes ALDH1L1 and PKM2 were overexpressed in glioma. We discovered that the anti-alcoholism drug disulfiram (DSF) can intervene in the tumor energy metabolism by inhibiting ATP supply via an alternative pathway, of which ALDH1L1 is an essential enzyme in the 10-formyl-tetrahydrofolate-NADH-ATP metabolism axis. We thus proposed a dual-inhibition strategy by using a combination therapy of a PKM2 inhibitor shikonin (SHK) and an ALDH1L1 inhibitor DSF. By simultaneously inhibiting glycolysis and NADH-ATP metabolism, the ATP generation in the tumor cells can be efficiently cut down. A BBB-penetrating hybrid albumin/lactoferrin nanosystem (termed BSA/LF NP) was developed for biomimetic codelivery of DSF/SHK for anti-glioma therapy. Due to the overexpression of SPARC and LRP-1 in both the BBB and glioma cells, the BSA/LF NP could efficiently enter the glioma. More importantly, it can deliver a fixed-dose ratio of DSF and SHK to the glioma, providing a basis for synergistic effect in combination therapy. The BSA/LF NP effectively prolonged the survival of glioma mice by interactive modulation of energy metabolism (via both glycolysis and NADH-ATP pathways) and immune microenvironment. The work provided a promising glioma-targeting strategy for a fixed-dose combination and a potent ATP-depletion treatment.